1969
DOI: 10.1113/jphysiol.1969.sp008968
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic inhibition of the monosynaptic reflex by vibration

Abstract: SUMMARYIn cats, the monosynaptic reflex (MSR) elicited from L 7 or S1 dorsal roots, or from the tibial nerve (H reflex) was suppressed by vibration at 50-500 c/s of the hind limb with innervation intact. The MSR was not suppressed by selective vibration of cutaneous receptors, and suppression was still observed after the hind limb was skinned. In contrast, the phenomenon disappeared when all muscle nerves were crushed.Suppression of the MSR by vibration was shown to be mediated by presynaptic inhibition by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0
4

Year Published

1975
1975
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(78 citation statements)
references
References 19 publications
5
69
0
4
Order By: Relevance
“…42,43 Gil li es et al showed that the H-ref lex was not sup pres sed by the se lec ti ve vib ra ti on of cu ta ne o us re cep tors, and that this sup pres si on was still ob ser ved af ter the hind limb was skin ned in cats. 36 Cody et al and Martin et al al so sho wed that the vib ra ti on of cu ta ne o us re cep tors did not ca u se any sig ni fi cant ef fect on the ref lex res pon se. 18,20 Jo int re cep tor af fe rents of ten res pond in both di rec ti ons (e.g.…”
Section: Po Ten Ti Al Ne U Ro Lo Gi Cal Mec Ha Nisms Of Vib Ra Ti On-mentioning
confidence: 99%
See 2 more Smart Citations
“…42,43 Gil li es et al showed that the H-ref lex was not sup pres sed by the se lec ti ve vib ra ti on of cu ta ne o us re cep tors, and that this sup pres si on was still ob ser ved af ter the hind limb was skin ned in cats. 36 Cody et al and Martin et al al so sho wed that the vib ra ti on of cu ta ne o us re cep tors did not ca u se any sig ni fi cant ef fect on the ref lex res pon se. 18,20 Jo int re cep tor af fe rents of ten res pond in both di rec ti ons (e.g.…”
Section: Po Ten Ti Al Ne U Ro Lo Gi Cal Mec Ha Nisms Of Vib Ra Ti On-mentioning
confidence: 99%
“…It is im pro bab le that se con dary spind le en dings and Gol gi ten don or gans play any part in H-ref lex suppres si on. 35,36,39,44 BO NE MEC HA NO RE CEP TORS AND AF FE RENTS An in cre a se in musc le elec tri cal ac ti vity at rest indi ca tes an in cre a se in mo tor ne u ron po ol ac ti va tion. 25,37 In the pre sent study, it was fo und that the re was an in cre a se in EMG ac ti vity at rest du ring vib ra ti on, and that the UD ra di us BMC might ha ve had an ef fect on this in cre a se.…”
Section: Po Ten Ti Al Ne U Ro Lo Gi Cal Mec Ha Nisms Of Vib Ra Ti On-mentioning
confidence: 99%
See 1 more Smart Citation
“…The major finding of previous studies is that vibratory stimulation can be used to reduce the excitation of α motoneurons. This theoretical background indicates that vibratory stimulation applied to the muscle spindle provokes a decrease in the excitation of monosynaptic and oligosynaptic reflexes, resulting in presynaptic inhibition of group I and II afferent fibers [20][21][22] . We postulate that the inhibition of group I and group II afferents from the ankle joint is possible by applying vibration from the cutaneous to the ankle joint.…”
Section: Introductionmentioning
confidence: 99%
“…7 On the contrary, it was shown that the vibration treatment did not enhance the muscle spindle sensitivity and led to presynaptic inhibition of muscle spindle group Ia afferents. [8][9][10][11] As an alternative to tonic vibration reflex, recently described bone myoregulation reflex has been suggested to explain the increased muscle strength and electrical activity induced by vibration. Through the bone myoregulation reflex, bone is sensitive to mechanical stimuli and can send mechanical input signals to central nervous system, resulting in neuronal stimulation of muscle activity.…”
mentioning
confidence: 99%